Contractors apprehension of doctrine of frustration and Force Majeure clause in construction contracts - Manivannan, Govin Kumar (2022)
The spread of Covid-19 had constrained the entire world to uphold the lockdown where all the business areas and daily activities were put on hold and new standards were embraced from around 2020 up to this point. The construction industry was one area that was seriously impacted by this pandemic, including Malaysia. Endless discussions regarding the Doctrine of frustration were brought forward regarding determining the Covid-19 impact on the contracting party who plan to seek relief using this clause. Thus, the purpose of this study is to investigate whether the Doctrine of frustration can be applied in light of the Covid-19 pandemic and the level of awareness of contractors regarding the Force Majeure clause in Malaysia. This study was carried out using a mixed methodology. This method encompasses of integrated literature review, and a questionnaire survey was used. A literature review on the Doctrine of frustration stated that, unlike Force Majeure clauses, the Court could only consider frustration in the absence of a Force Majeure clause. Various case analyses found that under section 57 of the Contracts Act 1950, a pandemic such as Covid-19 would not be sufficient to frustrate a contract. For the second method, various construction professionals distributed the questionnaire survey. Descriptive analyses were done from the survey data using IBM Statistical Package for Social Sciences (SPSS). This paper uncovers a varying degree of awareness of the Force Majeure clause, for the most part, because of an absence of Experience with managing Force Majeure. This study was finished with specific proposals to work on enforcing the Force Majeure clause for future statements.